A Comparative Analysis of the Approaches of Political Parties and Women’s Organizations in Turkey on Gender Equality and Women's Issues - Şen, A. Fulya (My University, 2021)
This paper deals with how gender inequality and the major issues facing women are represented in the\rpolicy texts of political parties and within the strategies of women’s organizations in Turkey. Thus, it\rattempts to reveal different and similar perspectives on the gender regime in the political and civic\rsphere. For this purpose, it utilizes the content analysis method to look for answers to the following\rquestions: What are the main foci of political parties and women’s organizations on women's issues?\rWhat are the policies of political parties and women’s organizations about the issues that women face\rin modern society? This paper compares political parties and women's organizations in terms of their\robjectives on gender equality and women’s rights. Thus, it will be possible to understand the approaches\rof the political parties and women's organizations on women's issues and the main themes of\rtheir discourses on women’s rights and to provide a holistic view of the inadequacies of policies on\rwomen’s rights and gender equality. The study concluded that political parties deal with women's\rissues on the basis of ideological priorities while the women’s civil society organizations and women’s\rrights activists aim at advancing women's rights.
Keywords: Siyasi Bilimler; Kadın Araştırmaları